PERAN GURU PENGGERAK DALAM IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DI SDN SENGON 01 KABUPATEN BATANG - Assidiq, Nur Alim (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2024)
This study aims to examine the role of mobilizing teachers in the implementation of the Independent Learning Curriculum at SDN Sengon 01. This curriculum changes the learning paradigm towards an inclusive model that focuses on developing the potential of students. Mobilizing teachers are faced with challenges and opportunities in supporting this change. The research method used is qualitative with a phenomenological approach, involving principals and mobilizing teachers as data sources. The results showed that mobilizing teachers act as mobilizers of learning communities, agents of change, forums for discussion and collaboration, creating a pleasant learning atmosphere, always developing themselves, and as motivators.